Long-Term Follow-Up of Patients With Tetralogy of Fallot and Implantable Cardioverter Defibrillator: The DAI-T4F Nationwide Registry. Issue 17 (27th October 2020) - Waldmann, Victor; Bouzeman, Abdeslam; Duthoit, Guillaume; Koutbi, Linda; Bessiere, Francis; Labombarda, Fabien; Marquié, Christelle; Gourraud, Jean Baptiste; Mondoly, Pierre; Sellal, Jean Marc; Bordachar, Pierre; Hermida, Alexis; et al.
Abstract : Background: Tetralogy of Fallot (TOF) is the most common cyanotic congenital heart disease, and sudden cardiac death represents an important mode of death in these patients. Data evaluating the implantable cardioverter defibrillator (ICD) in this patient population remain scarce. Methods: A Nationwide French Registry including all patients with tetralogy of Fallot with an ICD was initiated in 2010 by the French Institute of Health and Medical Research. The primary time to event end point was the time from ICD implantation to first appropriate ICD therapy. Secondary outcomes included ICD-related complications, heart transplantation, and death. Clinical events were centrally adjudicated by a blinded committee. Results: A total of 165 patients (mean age, 42.2±13.3 years, 70.1% males) were included from 40 centers, including 104 (63.0%) in secondary prevention. During a median (interquartile range) follow-up of 6.8 (2.5–11.4) years, 78 (47.3%) patients received at least 1 appropriate ICD therapy. The annual incidence of the primary outcome was 10.5% (7.1% and 12.5% in primary and secondary prevention, respectively; P =0.03). Overall, 71 (43.0%) patients presented with at least 1 ICD complication, including inappropriate shocks in 42 (25.5%) patients and lead dysfunction in 36 (21.8%) patients. Among 61 (37.0%) patients in primary prevention, the annual rate of appropriate ICD therapies was 4.1%, 5.3%, 9.5%, and 13.3% in patients with, respectively, 0, 1, 2, or ≥3 guidelines-recommended risk factors. QRS fragmentation was the only independent predictor of appropriate ICD therapies (hazard ratio, 3.47 [95% CI, 1.19–10.11]), and its integration in a model with current criteria increased the 5-year time-dependent area under the curve from 0.68 to 0.81 ( P =0.006). Patients with congestive heart failure or reduced left ventricular ejection fraction had a higher risk of nonarrhythmic death or heart transplantation (hazard ratio, 11.01 [95% CI, 2.96–40.95]). Conclusions: Patients with tetralogy of Fallot and an ICD experience high rates of appropriate therapies, including those implanted in primary prevention. The considerable long-term burden of ICD-related complications, however, underlines the need for careful candidate selection. A combination of easy-to-use criteria including QRS fragmentation might improve risk stratification. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03837574. Abstract : Supplemental Digital Content is available in the text.